Risk Factor of Dietary Habit with Cholelithiasis - Lysandra, Annora Zerlina; Putri Wairooy, Nabilah Azzah; Ifadha, Rania Tasya; Ramainaldo S., Adra Achirultan; Albright, Ivan Angelo; Izzah, Alifah Fajriyyatul; Rahma M., Viky Nafi'ah; Lestari, Pudji (Universitas Airlangga, 2022)
Cholelithiasis affects 10-15% of the adult population. There are four main factors commonly associated with cholelithiasis abbreviated as